(untitled) (Tempo e Argumento, 2009)
There isa “Uruguayan Diaspora”, which is quantitatively relevant in relation to the population of the country, and there are a significant number of Uruguayan citizens, not yet quantified, who are related to the country ́s projects. Among other characteristics, the Uruguayan Diaspora shows an evident desire to closely accompany the evolution of the Uruguayan reality. This interest is clearly expressed in the permanent search for information of what is going on in Uruguay, many times channeled through the growing number of organizations that operate as a link between the different emigrants’ communities and the country, together with the expressed interest ofthe new Administration of the country which took office in 2005, with the creation of the Consulting Councils, organizations of Uruguayan citizens belonging to different colonies abroad which constitute the link, bond and representatives of the colony with the country. This article intends to show the present situation and demonstrate, through interviews conducted with several Uruguayan citizens residing abroad, that this is an essential aspect in the identity building, allowing the reinforcement of the original ties, commitment and participation within the Latin American framework.